The sand fly fauna (Diptera: Psychodidae: Phlebotominae) of a focus of cutaneous leishmaniasis in Ilhéus, state of Bahia, Brazil - Alfredo CR Azevedo; Maurício L Vilela; Nataly A Souza; Claudia A Andrade-Coelho; André F Barbosa; Antônio LS Firmo; Elizabeth F Rangel (Memorias do Instituto Oswaldo Cruz, 1996)
The municipality of Ilhéus, State of Bahia, has a focus of cutaneous leishmaniasis where entomological studies were carried out to determine the sand fly species and their habits. Lutzomyia migonei, L. sallesi, L. tupynambai, L. schreiberi, L. intermedia, L. whitmani, L. yuilli yuilli, L. fischeri, L. pessoai, L. shannoni and L. misionensis were identified. Lutzomyia whitmani was the predominant species. Specimens were collected indoors, at peridomestic sites, in the cocoa plantations and in other types of collections. Females fed readily on humans and were attracted to domestic animals. Our evidence suggests that L. whitmani is a probable vector.